Ben Siras View of Women: A Literary Analysis - Trenchard, Warren C. (Brown Judaic Studies, 2020)
An ""analysis of gender not only in the biblical (Apocrypha) book of Sirach but in literature from the Second Temple period more broadly. Trenchard's study remains important for thinking about ""misogyny"" in the ancient world, in all of its literary as well as cultural dimensions.""--Publishers' preface.